Studying Short-Term and Long-Term Effects of OPEC Oil Basket Prices and Natural Gas on Liquefied Petroleum Gas (LPG) Traded on Energy Exchange of Iran - Zahra Shiri; Hamid Taghizadeh; Ramiar Refaei (International Journal of Management, Accounting and Economics, 2017)
In this paper, we examine the short-term and long-term effects of OPEC oil basket prices and natural gas on liquefied petroleum gas (LPG) traded on Energy Exchange of Iran. tests of convergence (integration) and causality of variables have been used for 2-year period, from May 22, 2014 to July 21, 2016. The results of the study based on long-term relationship show that an increase of 1 percent in the logarithm of OPEC oil basket prices decreases 17.24 percent of the logarithm of the price of LPG. The direction of causality is from OPEC oil basket prices to LPG. Moreover, 1% increase in natural gas prices logarithm will increase 26.52 percent of the logarithm of the price of LPG. The direction of causality is from natural gas to LPG. Estimating the relationship between short-term error corrections for the logarithm of the price of LPG also confirms no statistically significant error correction component.